The determinant factors affecting IPO pricing in Malaysia / Muhammad Hilmi Shaharudin - Shaharudin, Muhammad Hilmi (2015)
Each day companies around the world enter stock exchange for the first time. Purpose of this participation is to support required investments to continue their activities and develop their operations. This matter makes price of shares in the initial offerings a very considerable subject, in other word; price determined for their shares indicates true properties value and grants future development and growth opportunities. Considering importance of investments in stock exchange and importance of pricing to attract investors and success of suppliers, this research studies shares initial offering pricing and the determinant factors affecting it. There are many variables that will influence the IPO pricing. This paper aims to investigate the effects of firm age, earnings per share, price-earnings ratio, book-value per share, return on equity, and leverage towards the pricing of IPO. A database of IPOs listed on Bursa Malaysia during the period 2012-2015is considered for the study. Sample count includes the accepted companies in Bursa Malaysia.